Efficiency analysis for a grid-connected battery energy storage system. (2018) - Noyanbayev, N.K.; Forsyth, A.J.; Feehally, T.
Abstract: Efficiency is one of the key characteristics of grid-scale battery energy storage system (BESS) and it determines how much useful energy lost during operation. The University of Manchester has been commissioned with 240 kVA, 180 kWh lithium-ion BESS. This paper investigates round-trip efficiencies, comparing energy extracted from and returned to the grid, of the BESS for different operation modes. This is done by developing simulation switch-level model of power components of the BESS. The simulation is validated against hardware test results and used to identify optimum operation modes, which vary depending on SOC and charging and discharging power rates of the BESS.